2003
DOI: 10.1002/pola.10968
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic and hydrophobic surface patterns generated from hyperbranched fluoropolymer/linear polymer networks: Minimally adhesive coatings via the crosslinking of hyperbranched fluoropolymers

Abstract: Hyperbranched fluoropolymers (HBFPs), based on benzyl ether linkages and having a large number of pentafluorophenyl chain ends, were crosslinked by a reaction with diamino‐terminated poly(ethylene glycol) (PEG) or diamino‐terminated poly(dimethyl siloxane) (PDMS) to form hyperbranched–linear copolymer networks of different compositions, structures, and properties. The crosslinking reactions involved the nucleophilic aromatic substitution of the pentafluorophenyl para‐fluorines of HBFP by the amine functionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 41 publications
7
123
0
2
Order By: Relevance
“…[41] Crosslinking was afforded by the nucleophilic aromatic substitution of the para-fluorines of the pentafluorophenyl groups present in HBFP (I) by the amino termini of the PEG chains using a stoichiometric amount of diisopropylethyl amine (DIEA) in THF at a reflux for 20 h [Scheme 4(a)]. Moreover, Scheme 4 illustrates that in addition to the bifunctionality of the DA/PEG chains establishing bridging crosslinks between the hyperbranched macromolecules, monoattachment was possible, leaving a free amine endgroup, remaining after the reaction of only one of the two amino termini of the linear polymer chain.…”
Section: Crosslinking Of Hbfp Into Amphiphilic Network With Linear Pegmentioning
confidence: 97%
See 2 more Smart Citations
“…[41] Crosslinking was afforded by the nucleophilic aromatic substitution of the para-fluorines of the pentafluorophenyl groups present in HBFP (I) by the amino termini of the PEG chains using a stoichiometric amount of diisopropylethyl amine (DIEA) in THF at a reflux for 20 h [Scheme 4(a)]. Moreover, Scheme 4 illustrates that in addition to the bifunctionality of the DA/PEG chains establishing bridging crosslinks between the hyperbranched macromolecules, monoattachment was possible, leaving a free amine endgroup, remaining after the reaction of only one of the two amino termini of the linear polymer chain.…”
Section: Crosslinking Of Hbfp Into Amphiphilic Network With Linear Pegmentioning
confidence: 97%
“…The content of this feature article will build from these amphiphilic types of materials, with emphasis upon the production of amphiphilic crosslinked networks that combine all desired features of compositional and structural heterogeneity, being composed of HBFPs and linear PEG. [41][42][43] These materials were developed initially as non-toxic, anti-biofouling coatings for application in the marine environment, and they have demonstrated remarkable perormance toward this application. [44] Moreover, their complex morphologies were also found to provide nanochannels that exhibit unusual thermallypromoted release of volatile guest molecules, [45] and nanoscale confinement of water swollen within the materials to result in dramatically increased moduli.…”
Section: Feature Articlementioning
confidence: 99%
See 1 more Smart Citation
“…12 Research has demonstrated that two different algal species, one of which adhered strongly to hydrophobic surfaces, and the other, to hydrophilic surfaces, showed notably weak adhesion to the amphiphilic polymer surfaces. 12 Pioneer research in such binary systems comes from the work of Wooley and coworkers, [13][14][15] who reported amphiphilic polymer coatings prepared by the in situ phase separation and crosslinking of hyperbranched fluoropolymers and linear PEG networks for efficient antifouling coatings. Since then, surface-active block copolymers with fluoroalkyl side chains, amphiphilic semifluorinated block copolymers have been explored in antifouling coatings.…”
mentioning
confidence: 98%
“…For instance, Wooley and co-workers synthesized a series of polymeric networks comprising hyperbranched fluoropolymers and poly͑EG͒ chains and studied their resistance against a variety of proteins and zoospores of green fouling alga. [9][10][11] The group reported that the coating's performance depended on the chemical composition and the topographical heterogeneity of the surface. In another strategy, Krishnan et al used amphiphilic diblock copolymers comprising EG and fluorinate blocks.…”
Section: Introductionmentioning
confidence: 99%